2022
DOI: 10.1021/acscatal.2c01361
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Physicochemical Characterization, and Catalytic Evaluation of Fe3+-Containing SSZ-70 Zeolite

Abstract: Whereas one-dimensional, 10-membered ring zeolites are typically used for hydroisomerization, Fe3+-containing SSZ-70 (Fe-SSZ-70) shows remarkable isomerization selectivity for a zeolite containing 12- and partially blocked 14-membered rings, in addition to 10-membered rings. Fe-SSZ-70 was compared to Al3+-containing SSZ-70 (Al-SSZ-70) in constraint index and n-decane hydrocracking tests. Fe-SSZ-70 exhibited a 74% total isomer yield (64% yield of monobranched isomers and 10% cracking yield) at 85% conversion co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The coordination state and extent of aggregation of Fe species in as-synthesized, calcined, and H-type Fe-AEI zeolites were investigated by UV–vis spectroscopy (Figure a–c). The spectra of as-synthesized zeolites were dominated by two characteristic oxygen-to-metal charge-transfer bands around 212 and 240 nm, which were related to tetrahedral Fe 3+ species in the framework (Figure a). , Thus, we concluded that Fe 3+ was predominantly built into the zeolite framework by the isomorphous substitution of Si 4+ by Fe 3+ . Compared to the as-synthesized zeolites, the band at 240 nm shifted to 270 nm for the calcined samples, which is typical for octahedral Fe species (Figure b) .…”
Section: Resultsmentioning
confidence: 78%
“…The coordination state and extent of aggregation of Fe species in as-synthesized, calcined, and H-type Fe-AEI zeolites were investigated by UV–vis spectroscopy (Figure a–c). The spectra of as-synthesized zeolites were dominated by two characteristic oxygen-to-metal charge-transfer bands around 212 and 240 nm, which were related to tetrahedral Fe 3+ species in the framework (Figure a). , Thus, we concluded that Fe 3+ was predominantly built into the zeolite framework by the isomorphous substitution of Si 4+ by Fe 3+ . Compared to the as-synthesized zeolites, the band at 240 nm shifted to 270 nm for the calcined samples, which is typical for octahedral Fe species (Figure b) .…”
Section: Resultsmentioning
confidence: 78%
“…As can be seen in Figure 1 Be,f, Fe(0.03) −H(0.05) −9−CP and Fe(0.06) −H(0.07) −9−CP showed essentially two absorption bands located at ca. 210 and 272 nm, which were assigned to electronic transitions of the anion (e.g., O 2− ), that is, t 2g and e g orbitals of Fe 3+ within [FeO 4 ] − tetrahedra [ 9 , 28 ]. Obviously, these observations were associated with ligand to metal charge-transfer characteristics that involved the isolated four-coordinated and octahedral coordinated mononuclear Fe 3+ [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 shows the EPR spectra acquired at 77 K for Fe-substituted CPs. As can be seen, all samples presented two signals: a sharp signal at g = 4.3 assignable to tetrahedral Fe 3+ [ 28 ], and a broad signal at g = 2.0 assignable to octahedrally coordinated Fe 3+ in the non-framework positions. Their deformation was the same as profiles reported by Bordiga et al [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows an additional decrease in viscosity that could lead to a greater increase in the recovery factor. Studies have been reported on different metal-based catalysts (Fe, Co, Ni) [16][17][18]; however, it has been shown that Ni is the most active catalyst for the hydrocracking and hydrogenation of heavy components, while inhibiting condensation and recombination reactions, as demonstrated by Muneer et al in their study [2]. Several studies of hydrothermal upgrading of heavy oil using different catalysts have been performed [19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%